Korporatīvās kultūras ietekme uz darbinieku apmierinātību un lojalitāti IT uzņēmumi - Volochai, Iryna (Latvijas Universitāte, 2025)
This study investigates the influence of corporate culture on employee satisfaction and loyalty within the IT industry, a sector characterized by rapid innovation and intense competition for talent. Through a combination of theoretical analysis and empirical research, the thesis explores how key cultural dimensions—such as leadership communication, employee autonomy, recognition systems, psychological safety, work-life balance, and value alignment—shape employee attitudes and organizational commitment. The empirical component involved a quantitative survey of 112 IT professionals, analyzed using descriptive statistics and thematic content analysis. Results indicate that transparent communication, autonomy, and alignment between personal and organizational values significantly enhance job satisfaction and loyalty, while deficiencies in recognition and inclusivity present areas for improvement. The findings confirm that a positive corporate culture fosters higher employee engagement, reduces turnover, and contributes to organizational success. Practical recommendations include implementing leadership training, transparent recognition programs, and inclusive policies to strengthen corporate culture and retain talent in IT companies.
The Impact of Corporate Culture on Employee Satisfaction and Loyalty in IT Companies
Keywords: Ekonomika un uzņēmējdarbība; corporate culture; employee satisfaction; employee loyalty; IT industry; leadership communication